Makna “Bergizi” Dalam Persepsi Masyarakat Kota Depok Pada Program Makan Bergizi Gratis (MBG) - Desna Aryana Pratiwi; Amanda Devita Triana; Aflah Kanaya Noor; Nazwa Haliza Gunawan Azzahra (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2026)
The Free Nutritious Meals Program (MBG) is a national policy aimed at improving children’s nutritional quality and human resource development in Indonesia. This study aims to analysis how residents of Depok City interpret the concept of “nutritious” food within the MBG program. The study employs a qualitative approach based on a constructivist paradigm through interviews with parents, students, and community members. The analysis utilized Stuart Hall’s Encoding-Decoding theory and the Stimulus-Organism-Response model. The results indicate that the community interprets nutritious food not only based on nutritional content but also on cleanliness, freshness, taste, and family health experiences. There is a gap between government nutritional standards and community perceptions. Negative experiences regarding food quality erode public trust and lead to food waste behaviour within the MBG program.